Identification of ETV6-RUNX1-like and DUX4-rearranged subtypes in paediatric B-cell precursor acute lymphoblastic leukaemia - Henrik Lilljebjörn (Nature Portfolio, 2016)
The fusion of two genes during the pathogenesis of cancer can create oncogenes. In this study, the authors screen pediatric B-cell precursor acute lymphoblastic leukaemia samples for the presence of fusion genes and describe fusion genes that define new molecular subtypes of the disease